The students error’s in geometry problems based on mathematical connection ability - A S Prasetya; S Fatimah (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The purpose of this research was to describe students error’s in geometry problems based on mathematical connection ability. This study was qualitative research with subject consisted of twenty five students. The results showed that (1) the students comprehension for recognize and used relationships between ideas in mathematics still lack, (2) The lack of students comprehension in maked connection mathematical ideas, (3) students have difficulty in formed new mathematical ideas so as to produced a comprehensive relationship, (4) students have not been fullied able to recognized and applied one mathematical content to other mathematical content and environments outside mathematics.